The realm of non-profit organisations in Malaysia / Saunah Zainon, Ruhaya Atan and Yap Bee Wah - Zainon, Saunah; Atan, Ruhaya; Yap, Bee Wah (UiTM Press, 2023)
The realm of non-profit organisations in Malaysia discusses the essential elements of non-profit organisations (NPOs), emphasising important issues in terms of governance, framework as well as organisational background of charitable bodies. Each area is written in simple English and presented in a concise manner. Masters and doctoral students in the field of social responsibility, governance and the third sector of NPOs would find the book of valuable guidance, as the book was well researched based on the doctoral thesis of the author on NPOs in Malaysia, by using a practical approach on the challenges faced by NPOs, highlighting the case of Pertubuhan Kebajikan Anak Yatim Islam (PKAYIS). In Malaysia, NPOs must not comply with any mandatory regulations due to its tax-exempt status. This easy-to-read book provides the foundation in the wake of new regulations for NPOs as other developed countries.